FINE SEDIMENT INFILTRATION DYNAMICS IN A GRAVEL‐BED RIVER FOLLOWING A SEDIMENT PULSE. (6th February 2013) - Evans, E.; Wilcox, A. C.
ABSTRACT Pulses of fine sediment in gravel‐bedded rivers can cause extensive fine sediment infiltration (FSI) into void spaces in coarse bed material, potentially altering river morphodynamics and aquatic ecosystems. Previous work suggests a conceptual model of FSI whereby FSI occurs to a limited depth as a function of the relative grain size of bed sediment compared with infiltrating sediment and is influenced by fine sediment supply and local flow dynamics. Our study applies this conceptual model to a complex reach of a wandering, medium‐sized, gravel‐bed river to investigate the spatial and temporal controls on FSI. To constrain the timing of FSI, we use the release of contaminated sediment from an upstream dam removal and complementary field methods (bulk sampling, freeze cores and infiltration bags) to capture sediment across varied depositional settings. Our results indicate that, even in a morphologically complex reach, fine‐sediment content in the bed does not vary significantly among deposition settings or vertically below the bed surface. We also found that the most contaminated fine sediments released into our study river by a dam removal are not present within the bed material and that substrate has likely been reworked over the period between the release of contaminated sediment and sampling. Our observations also suggest that seals of fine sediment causing void pore space at depth, which have previously been associated with FSI, are not evident in our field area. This suggests that in natural systems, high sediment supply and mobile beds may limit seal formation and persistence. Copyright © 2013 John Wiley & Sons, Ltd.